ECHINOCOCCUS GRANULOSUS GENOTYPE G8 IN MAINE MOOSE (ALCES ALCES) - Lichtenwalner, Anne; Adhikari, Nirajan; Kantar, Lee; Jenkins, Emily; Schurer, Janna (Lakehead University, 2014)
During a 2012 survey of harvested moose (Alces alces) in Maine (USA), an incidental finding of hydatid cysts was found in 39% (21 of 54) of lung sets examined. Cytology of cyst contents was consistent with Echinococcus granulosus. The G8 genotype was identified based on PCR and DNA sequencing of a 470 base pair region of the NADH dehydrogenase subunit 1 (NAD1) mitochondrial gene. The hydatid cysts were the northern, or cervid genotype and this is the first confirmed report of E. granulosus in Maine moose. The Atlantic regions of the northern USA and Canada were not previously thought to be endemic regions for E. granulosus. It is presumed that either domestic dogs or eastern coyotes (Canis latrans) are the definitive host.